Generalized comparison of graph-based ranking algorithms for publications and authors - Sidiropoulos, Antonis; Manolopoulos, Yannis (The Journal of systems and software, 2006)
Citation analysis helps in evaluating the impact of scientific collections (journals and conferences), publications and scholar authors. In this paper we examine known algorithms that are currently used for Link Analysis Ranking, and present their weaknesses over specific examples. We also introduce new alternative methods specifically designed for citation graphs. We use the SCEAS system as a base platform to introduce these new methods and perform a generalized comparison of all methods. We also introduce an aggregate function for the generation of author ranking based on publication ranking. Finally, we try to evaluate the rank results based on the prizes of ‘ VLDB 10 Year Award’, ‘ SIGMOD Test of Time Award’ and ‘ SIGMOD E.F.Codd Innovations Award’.